A Performance Comparative Analysis of Block Based Compressive Sensing and Line Based Compressive Sensing - Ebrahim, M.; Adil, S. H.; Nawaz, D. (Engineering, Technology & Applied Science Research, 2018)
Compressive sensing (CS) is an innovative idea that has opened new areas for viable communication of correlated data. In this paper, a comparative performance analysis of two different variants of compressive sensing i.e. block based compressive sensing (BCS) and line based compressive censing (LCS) schemes is performed for natural images. The idea is to evaluate which variant performs better in terms of reconstruction quality and provides easy initial solution. The experimental analysis demonstrates that LCS scheme can enhance the image reconstruction at lower subrates by 0.5 dB to 2.5 dB, when compared to the BCS scheme.